Morbidity Profiles of Kerala and All-India: An Economic Perspective - M.H. Suryanarayana (Indira Gandhi Institute of Development Research, Mumbai WP-2008-007, 2008)
This study examines the economic profiles of morbidity by disease in Kerala and all- India by estimating Engel elasticities for diseases and classifying them as between those associated with affluence and deprivation. Morbidity rates, in general, are more for the rich than for the poor. There could be factors other than income, which influence the morbidity rates as revealed by horizontal pseudo-Lorenz curves for distribution of reported total morbidity across households. That morbidity rates are higher for the rich than for the poor households does not hold uniformly valid at the level of individual diseases. This is borne out by pseudo-Lorenz curves for diseasespecific morbidity. Pseudo-Lorenz curves lay above/below the Line of Equal Distribution depending upon the nature of diseases. The sub-set of undiagnosed diseases is a poor man's disease in both rural and urban all-India but only in urban Kerala. To avoid Type II errors in targeting medical facilities, it would be useful to identify those diseases, which afflict the rich proportionately more, that is, diseases with Engel elasticities more than one. Such diseases are virtually insignificant in Kerala. They account for 1.23 and 1.75 per cent of reported morbidity cases in rural and urban Kerala respectively. As regards all-India, they have significant presence. Their respective shares in total rural and urban morbidity cases are 7.83 and 6.83 per cent. Generally coronary heart diseases, diabetes and hypertension are considered as life style diseases. Among them, only diabetes mellitus has elasticity greater than one for rural and urban all-India; heart disease and hypertension too have elasticities greater than one only for rural all-India. As regards Kerala, none of them are luxury diseases. This could also be interpreted to represent a process whereby the diseases of affluence and deprivation converge in Kerala. In other words, this may represent a shift a in the epidemiology of diseases in Kerala